CHANGES IN ORGANOLEPTIC CHARACTERISTICS OF NORI FROM Gracilaria sp. DURING STORAGE WITH DIFFERENT TYPES OF PACKAGING - Evi Liviawaty; Sapinatun Namira; Subiyanto Subiyanto; Eddy Afrianto (International Journal of Research in Community Services, 2021)
This research was conducted at the Laboratory of Fisheries Products Processing, Faculty of Fisheries and Marine Sciences, Padjadjaran University, Jatinangor. The purpose of this research is to test the quality of Gracilaria sp. packed with various types of packaging during the 25oC dan 35oC temperature storage period. The method used in this research is an experimental method with 2 treatments, namely (1) packaging type factors, namely polyethylene (PE), polypropylene (PP), and aluminum foil packaging and (2) storage time factors, namely 1, 7, 14, 21, 28, and 35 days. The test carried out in each treatment is the organoleptic test using the scoring test by standard panelists. The results of the organoleptic research were analyzed using the average data of the appearance, aroma, texture and taste scoring test to see the differences between treatments. The scoring test results show that the treatment of aluminum foil packaging can maintain the appearance, aroma, texture and taste parameters until the 35th day when compared with other packaging treatments.